2019
DOI: 10.1177/0361198119845899
|View full text |Cite
|
Sign up to set email alerts
|

Improved Support Vector Machine Models for Work Zone Crash Injury Severity Prediction and Analysis

Abstract: Work zones are a high priority issue in the field of road transportation because of their impacts on traffic safety. A better understanding of work zone crashes can help to identify the contributing factors and countermeasures to enhance roadway safety. This study investigates the prediction of work zone crash severity and the contributing factors by employing a parametric approach using the mixed logit modeling framework and a non-parametric machine learning approach using the support vector machine (SVM). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(31 citation statements)
references
References 55 publications
(64 reference statements)
0
31
0
Order By: Relevance
“…ML methods are more flexible with no or fewer model assumptions for input variables, and also have better fitting characteristics. Some of the commonly used ML approaches used in crash injury severity prediction include artificial neural networks (ANN) [ 58 , 59 , 60 ], random forest [ 54 , 61 , 62 ], support vector machines (SVM) [ 51 , 63 , 64 ], naïve Bayes [ 65 , 66 , 67 ], K-means clustering (KC) [ 68 , 69 , 70 ], and decision trees (DT) [ 71 , 72 , 73 ].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…ML methods are more flexible with no or fewer model assumptions for input variables, and also have better fitting characteristics. Some of the commonly used ML approaches used in crash injury severity prediction include artificial neural networks (ANN) [ 58 , 59 , 60 ], random forest [ 54 , 61 , 62 ], support vector machines (SVM) [ 51 , 63 , 64 ], naïve Bayes [ 65 , 66 , 67 ], K-means clustering (KC) [ 68 , 69 , 70 ], and decision trees (DT) [ 71 , 72 , 73 ].…”
Section: Related Workmentioning
confidence: 99%
“…An ordered probit model was also used as a benchmark to validate the RF model. Mokhtarimousav et al compared the SVM and random parameter mixed logit models for the severity prediction of work zone crashes [ 64 ]. Empirical findings revealed that prediction accuracy from SVM outperformed the mixed logit model.…”
Section: Related Workmentioning
confidence: 99%
“…The quality assessment comprises a broad set of performance metrics for recognizing the best model. In other similar researches, the Recall is usually accompanied by Precision [22] and F1-Score [23].…”
Section: Purposementioning
confidence: 99%
“…Apart from the structural merits of ABC implementations, as it said earlier, it also has a considerable impact on roadway safety compared to on-site bridge construction. The effect of work zone presence on crash severity using sophisticated machine learning techniques has been recently investigated by Mokhtarimousavi et al (2019). In their study, different contributing factors that affect injury severity due to work zone presence have been identified and statistically analyzed.…”
Section: Accelerated Bridge Construction (Abc)mentioning
confidence: 99%